Notas fitogeográficas sobre el Quercus oleoides Cham. y Schlecht - Montoya Maquin, J.M. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Based on bibliographic and floristic records, the distribution area of Quercus oleoides Cham & Schlecht. has been determined for the continent and in more detail for Costa Rica. The physiography, the geology, the soils, and the climate of the area occupied by this species are described, and the ecology and taxonomy of the species in Costa Rica are discussed. The analogies between the areas of Costa Rica and of the rest of the continent have been established